2015
DOI: 10.1007/s11745-015-4075-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Serum and Hypoxia on Incorporation of [14C]‐d‐Glucose or [14C]‐l‐Glutamine into Lipids and Lactate in Murine Glioblastoma Cells

Abstract: Glucose and glutamine are essential energy metabolites for brain tumor growth and survival under both normoxic and hypoxic conditions. Both metabolites can contribute their carbons to lipid biosynthesis. We used uniformly labeled [(14)C]-U-D-glucose and [(14)C]-U-L-glutamine to examine the profile of de novo lipid biosynthesis in the VM-M3 murine glioblastoma cells. The major lipids synthesized included phosphatidylcholine (PtdCho), phosphatidylethanolamine (EtnGpl), phosphatidylinositol (PtdIns), phosphatidyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 86 publications
2
24
0
Order By: Relevance
“…VM-M3 cells are derived from an extremely aggressive spontaneous mouse brain tumor and exhibit a dependency on glycolytic metabolism [41, 42]. We have previously established that this tumor is susceptible to therapeutic metabolic modulation [4345].…”
Section: Discussionmentioning
confidence: 99%
“…VM-M3 cells are derived from an extremely aggressive spontaneous mouse brain tumor and exhibit a dependency on glycolytic metabolism [41, 42]. We have previously established that this tumor is susceptible to therapeutic metabolic modulation [4345].…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine metabolism can produce ATP from the TCA cycle under aerobic conditions. Glutamine is also a nitrogen donor for nucleotide biosynthesis and can serve as precursor for lipid synthesis under hypoxic conditions [ 104 , 105 ]. We also found that only minor amounts of glutamine are metabolized to lactic acid under either normoxia or hypoxia in the VM-M3 invasive glioblastoma cells consistent with findings in other tumor cells [ 105 107 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many tumor cells including breast cancer cells will store fatty acids as lipid droplets (166,171,172). Lipid droplet storage is considered a protection mechanism from the lethal effects of saturated fatty acids in cells that cannot metabolize fats for energy (171)(172)(173)(174). If tumor cells could use fatty acids for growth, then water-only fasting and calorie restricted ketogenic diets should accelerate tumor growth, as these dietary changes elevate free fatty acids in the blood (175,176).…”
Section: Ketogenic Metabolic Therapymentioning
confidence: 99%